1, 3, 6, 8-Pyrenetetrasulfonic acid anchored doping to prepare solution-processable polyaniline for electrochromic supercapacitors. (29th April 2021) - Li, Man; Tao, Chongxin; Zhu, Guanqun; Zhang, Huijun; Lin, Baoping; Zhang, Xueqin; Yang, Hong; Guo, Lingxiang; Sun, Ying
Abstract : A new strategy to improve the ion transmission and stability of ESCs by introducing an anchored dopant during the polymerization of PANI has been proposed. Abstract : Integrating electrochromism into supercapacitors can provide multifunctional electrochromic supercapacitors (ESCs) for smart windows and portable and wearable electronics. Polyaniline (PANI) as the most promising electrode material for ESCs is limited by its poor solution processability and inferior cycling stability. The strategy we propose here is to add 1, 3, 6, 8-pyrenetetrasulfonic acid (1, 3, 6, 8-Psas) as an anchored dopant during the polymerization of PANI. Its large steric hindrance can play a role in inter-chain support and reduce the effect of inter-chain interaction for obtaining excellent solution processability. In addition, 1, 3, 6, 8-Psas can also act as a crosslinking agent, which can adjust the morphology of PANI to provide a composite electrode with a rich pore structure for increased contact area with electrolyte and thus improved ion transmission. The area specific capacitance of the original PANI-WO3 /FTO composite electrode calculated from the CV curve at 100 mV s −1 is 38.71 mF cm −2, while the 1, 3, 6, 8-Psas doped PANI-WO3 /FTO composite electrode is 72.11 mF cm −2, which indicates that the introduction of 1, 3, 6, 8-Psas could greatly improve the electrochemical properties of the solution processed PANI. The capacitance retention rate of the composite electrode with 1, 3, 6, 8-Psas as the anchor doping agent is 70.12% after 1000 cycles, while the capacitance retention rate of the PANI-WO3 /FTO electrode with 1000 cycles is only 43.34%, which indicates that the anchoring effect of 1, 3, 6, 8-Psas can support the linking of PANI and prevent the impact failure of the PANI chain skeleton.